The Influence of Transformational Leadership on Employee Performance with Job Satisfaction and Organizational Commitment as Mediation Variables - Andani Artanti Yodani; Santi Rimadias (Indonesia Banking School, 2022)
This study aims to analyze the effect of transformational leadership on employee performance with job sat-isfaction and organizational commitment as mediating variables with the object of research being perma-nent employees of PT. Pegadaian (Persero) Regional Office VIII Jakarta 1 Bogor Area. This research is quantitative research. The sample used in the study was 205 respondents. The Structural Equation Model (SEM) technique and Amos 22 software are both used in the investigation. The findings show that trans-formational leadership has a beneficial effect on job satisfaction, organizational commitment, job satisfac-tion, and employee performance. It was discovered, however, that neither transformational leadership nor organizational commitment had any effect on employee performance as measured by job satisfaction or organizational commitment.